Floristic changes induced by fire on Pinus sylvestris plantations in northwest of Spain - Nuñez, R.M.=700 1 Calvo, L.; Pando, V.; Bravo, F.
(En, Es)
ilus., 51 ref.
Keywords: GERMINACION; COMPOSICION BOTANICA; REBROTE; INCENDIOS FORESTALES; ESPAÑA; INVESTIGACION AGRARIA: SISTEMAS Y RECURSOS FORESTALES